Nitrogen-sulfur co-coordinated monatomic solid base catalyst as well as preparation and application thereof
A nitrogen-sulfur co-coordinated single-atom solid base catalyst addresses the aggregation and stability issues of traditional catalysts by enhancing interactions and stabilizing active sites, achieving high catalytic efficiency and cyclic stability in transesterification reactions.
Patent Information
- Application Number
- CN202411213879.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional supported solid base catalysts used in the industrial production of dimethyl carbonate suffer from easy aggregation and loss of active sites, leading to poor activity and cyclic stability, limiting their application in base-catalyzed reactions such as transesterification.
A nitrogen-sulfur co-coordinated single-atom solid base catalyst is developed by synthesizing a polymer, carbonizing it, and introducing an active component precursor and sulfur source through impregnation, forming a catalyst with strong interactions between basic sites and the carrier, stabilizing the dispersion state and reducing active site loss.
The catalyst exhibits high catalytic efficiency and cyclic stability, with enhanced active site density and interaction, improving the catalytic performance and maintaining yield over multiple reaction cycles.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of industrial catalysis technology, and in particular to a nitrogen-sulfur co-coordinated single-atom solid base catalyst and its preparation and application; in particular, to a single-atom solid base catalyst for preparing dimethyl carbonate through an ester exchange reaction and its preparation method. Background Art
[0002] As a low-toxic, green and environmentally friendly organic chemical product, dimethyl carbonate is widely used in important fields such as lithium battery electrolyte, gasoline additives and polycarbonate production due to its high oxygen content, boiling point and good solubility. It is known as the "new cornerstone" and "green chemical product" of organic synthesis in the 21st century. The main methods for industrial production of dimethyl carbonate are methanol oxidation carbonylation and transesterification. The transesterification method, which reacts ethylene carbonate with methanol to produce dimethyl carbonate and co-produce ethylene glycol, has attracted widespread attention due to its advantages such as mild reaction conditions, mature process and simple treatment of three wastes. However, the traditional supported solid base widely used in industry currently has problems such as easy aggregation and loss of active sites, resulting in poor activity and poor cyclic stability, which limits its application. Based on the above problems, it is of great significance to prepare a single-atom solid base catalyst with high activity and high stability, and apply it to base-catalyzed reactions such as transesterification. Summary of the invention
[0003] The purpose of the present invention is to provide a nitrogen-sulfur co-coordinated single-atom solid base catalyst in order to improve the deficiencies of the prior art. Another purpose of the present invention is to provide a method for preparing the above single-atom solid base catalyst. Another purpose of the present invention is to provide the application of the above catalyst. First, a polymer is synthesized, and then it is carbonized to obtain a nitrogen-doped carbon material. Then, an active component precursor and a sulfur source are introduced into a carrier by an impregnation method. During the high-temperature treatment process, sulfur atoms are in-situ doped onto the carrier, and finally a nitrogen-sulfur co-coordinated single-atom solid base catalyst is obtained, which can catalyze the reaction of ethylene carbonate and methanol to produce dimethyl carbonate under mild conditions.
[0004] The technical scheme of the present invention is: in view of the problems that the liquid alkali widely used in the current ester exchange reaction process for preparing dimethyl carbonate is not easy to recycle, is highly corrosive to the equipment, and the basic sites of the traditional supported solid alkali catalyst are easy to aggregate and lose, resulting in poor activity and stability, the present invention designs a nitrogen-sulfur co-coordinated single-atom solid alkali catalyst. The introduction of nitrogen and sulfur heteroatoms can change the coordination environment of metal single atoms, form strong interactions with alkali metals / alkaline earth metals, enhance the interaction between the basic sites and the carrier, and then stabilize the dispersion state of the single atoms on the carrier surface, prevent the migration and agglomeration of active sites, and reduce the loss of active sites during recycling.
[0005] The specific technical solution of the present invention is: a nitrogen-sulfur co-coordinated single-atom solid base catalyst, characterized in that it is composed of a nitrogen-sulfur co-doped carbon carrier and an active component, wherein the active component is a single alkali metal or alkaline earth metal atom.
[0006] Preferably, the nitrogen content of the nitrogen-sulfur co-doped carbon carrier is 5% to 15% by mass, and the sulfur content is 1% to 5% by mass. Using the sulfur-modified polymer-derived nitrogen-doped carbon as a carrier, a nitrogen-sulfur co-coordinated single-atom solid base catalyst is formed during high-temperature activation.
[0007] Preferably, the active component is calcium, sodium or potassium atom; wherein the mass content of the active component is 0.5% to 3%.
[0008] The present invention also provides a method for preparing the above-mentioned single-atom solid base catalyst, the steps of which are as follows:
[0009] (1) taking a certain amount of polymer precursors A and B and dissolving them in an organic solvent (just dissolving), adding ferric chloride catalyst, heating in a water bath and stirring the reaction for a period of time to obtain a solid precipitate, filtering and drying the obtained sample to obtain the polymer; wherein the precursor A is mesitylene or pyrrole; the precursor B is one of methylal, α,α'-dichloro-p-xylene, 1,3,5-tri-bromomethylbenzene or mesitylene alcohol;
[0010] (2) The polymer is carbonized at high temperature in an inert atmosphere to obtain nitrogen-doped carbon, and then a sulfur source precursor and an active metal precursor are introduced by an impregnation method; the impregnated sample is evaporated in a water bath and then calcined at high temperature in an inert gas to finally form a nitrogen-sulfur co-coordinated single-atom solid base catalyst.
[0011] Preferably, the organic solvent in step (1) is dichloromethane or tetrahydrofuran; the molar ratio of polymer precursor A to B is 0.6-1.5:1; the molar ratio of catalyst to polymer precursor A is 1-2:1; the reaction temperature is 60-80°C, and the reaction time is 36-90h.
[0012] Preferably, the temperature of the high temperature carbonization in step (2) is 450-500°C, and the time of the high temperature carbonization is 2-2.5 hours; the sulfur source precursor is thiophene or thiourea; the mass ratio of the sulfur source precursor to the nitrogen-doped carbon is 2-3.5:1; the active metal precursor is potassium nitrate, sodium nitrate or calcium nitrate, and the mass ratio of the active metal precursor to the nitrogen-doped carbon is 0.2-0.35:1; the temperature of the high temperature calcination is 800-900°C, and the time of the high temperature calcination is 2-2.5 hours. The inert gas is nitrogen or argon.
[0013] The present invention also provides an application of the above-mentioned single-atom solid base catalyst in the ester exchange reaction to produce dimethyl carbonate. The specific reaction steps are as follows: methanol and ethylene carbonate are placed in a double-necked reaction bottle equipped with a condenser, and after heating to a specific temperature in a water bath, a catalyst is added to start the reaction, and the product is obtained after a period of reaction.
[0014] The invention catalyzes methanol and ethylene carbonate to undergo ester exchange reaction to generate dimethyl carbonate; preferably, the mass ratio of methanol to ethylene carbonate is 2-2.5:1; the mass ratio of catalyst dosage to ethylene carbonate is 0.04-0.12:1; the reaction temperature is 65-85°C, and the reaction time is 3.5-6.5h under normal pressure condensation reflux conditions.
[0015] Beneficial effects: The single-atom solid base catalyst of the present invention is a novel solid base catalyst with highly dispersed alkaline sites and good cyclic stability. The sulfur precursor and active metal precursor are introduced into nitrogen-doped carbon by a one-pot method and in-situ doping is performed under high temperature to obtain a nitrogen-sulfur co-coordinated single-atom solid base catalyst, which has the following advantages:
[0016] (1) High catalytic efficiency: The introduction of heteroatom nitrogen and sulfur can significantly increase the active site density of the catalyst. Heteroatom doping can adjust the electronic structure of single-atom catalysts, providing more anchoring sites for the introduction of active components, thereby improving catalytic performance.
[0017] (2) The preparation process is simple: the sulfur source precursor and the active metal precursor are added in a one-pot method, and the nitrogen and sulfur atoms are in situ doped onto the support during high-temperature treatment, ultimately obtaining a nitrogen-sulfur co-coordinated single-atom solid base catalyst.
[0018] (3) High cyclic stability: Nitrogen-sulfur co-coordination can enhance the cyclic stability of single-atom catalysts, strengthen the interaction between active sites and carriers, reduce the loss of active sites during the reaction, and improve the cyclic stability of the catalyst. DETAILED DESCRIPTION
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0022] Embodiment 1:
[0023] (1) Take 2 mmol of mesitylene and 3 mmol of methylal and dissolve them in 140 mL of dichloroethane, add 2 mmol of ferric chloride, place in a 60°C water bath and heat with stirring for 40 h to obtain a solid precipitate. The sample obtained after filtering, washing and drying is polymer A, which is placed in an argon atmosphere at 500°C for 2 h to obtain a nitrogen-doped carbon sample.
[0024] (2) Weigh 0.45g thiourea and 0.05g calcium nitrate into a beaker, add 20mL ethanol to completely dissolve them, then add 0.2g nitrogen-doped carbon, stir at room temperature for 12h, evaporate in a water bath, and calcine the obtained sample at 800℃ in an argon atmosphere for 2h. After naturally cooling to room temperature, a single-atom calcium solid base catalyst (sample 1-1) is obtained, in which the mass content of nitrogen is 5.1%, the mass content of sulfur is 1.05%, and the mass content of active components is 0.53%. For the convenience of comparison, comparative samples are prepared by the same preparation method: Sample 1-2 is a sample without the addition of thiourea, that is, a single-atom solid base sample coordinated with nitrogen.
[0025] (3) The obtained catalyst was tested for catalytic transesterification reaction. 4.4g of ethylene carbonate, 10.6g of anhydrous methanol and 0.2g of catalyst were added to a double-necked flask. The reaction was stirred in a water bath at 80℃ for 4h. The supernatant was filtered and the yield was analyzed by gas chromatography. After the reaction, the catalyst was recovered and activated at high temperature and a cycle experiment was carried out. The results showed that the yield of dimethyl carbonate of sample 1-1 was 41.3%, while the yield of sample 1-2 was 34.2%, which indicates that the single-atom solid base coordinated by nitrogen and sulfur has a higher catalytic activity. At the same time, after five cycles of use, the yield of sample 1-1 did not show a significant decrease, indicating that the introduction of heteroatoms anchored the calcium atom on the carrier well, giving it good cycle stability.
[0026] Embodiment 2:
[0027] (1) Take 2 mmol of mesitylene and 3 mmol of α,α'-dichloro-p-xylene and dissolve them in 110 mL of dichloroethane, add 2 mmol of ferric chloride, place in a 75 °C water bath and heat with stirring for 90 h to obtain a solid precipitate. The sample obtained after filtering, washing and drying is polymer ethylene, which is carbonized at 500 °C for 2 h in an argon atmosphere to obtain a nitrogen-doped carbon sample.
[0028] (2) Weigh 0.6g thiourea and 0.05g sodium nitrate in a beaker, add 20mL ethanol to completely dissolve them, then add 0.2g nitrogen-doped carbon, stir at room temperature for 12h and evaporate in a water bath, and treat the obtained sample at 900℃ for 2h in an argon atmosphere. After naturally cooling to room temperature, a single-atom sodium solid base catalyst (sample 2-1) is obtained, in which the mass content of nitrogen is 10.8%, the mass content of sulfur is 2.2%, and the mass content of active components is 1.3%. For the convenience of comparison, a comparative sample is prepared by the same preparation method: Sample 2-2 is a single-atom solid base sample without the addition of thiourea, i.e., nitrogen coordination.
[0029] (3) The obtained catalyst was tested for catalytic transesterification reaction. 4.4g of ethylene carbonate, 9.6g of anhydrous methanol and 0.5g of catalyst were added to a double-necked flask. The reaction was stirred in a water bath at 70℃ for 4h. The supernatant was filtered and the yield was analyzed by gas chromatography. After the reaction, the catalyst was recovered and activated at high temperature and a cycle experiment was carried out. The results showed that the yield of dimethyl carbonate of sample 2-1 was 46.9%, while the yield of sample 2-2 was 41.5%, which indicated that the single-atom solid base with nitrogen and sulfur co-coordination had higher catalytic activity. At the same time, after five cycles of use, the yield of sample 2-1 did not show a significant decrease, indicating that the introduction of heteroatoms anchored the sodium atom on the carrier well, giving it good cycle stability.
[0030] Embodiment 3:
[0031] (1) 3 mmol of pyrrole and 2 mmol of isotribenzyl alcohol were dissolved in 145 mL of dichloroethane, and 6 mmol of ferric chloride was added. The mixture was placed in a 75°C water bath and heated with stirring for 90 h to obtain a solid precipitate. The sample obtained after filtering, washing, and drying was polymer C, which was calcined in an argon atmosphere at 480°C for 2.5 h to obtain a nitrogen-doped carbon sample.
[0032] (2) Weigh 0.65g thiophene and 0.05g calcium nitrate into a beaker, add 20mL ethanol to completely dissolve it, then add 0.2g nitrogen-doped carbon, stir at room temperature for 12h and evaporate in a water bath, and place the obtained sample in an argon atmosphere and calcine at 900℃ for 2h. After naturally cooling to room temperature, a single-atom calcium solid base catalyst (sample 3-1) is obtained, in which the mass content of nitrogen is 12.1%, the mass content of sulfur is 3.2%, and the mass content of active components is 1.8%. For the convenience of comparison, a comparative sample is prepared by the same preparation method: Sample 3-2 is a single-atom sample coordinated with nitrogen without the addition of thiophene.
[0033] (2) The obtained catalyst was tested for catalytic transesterification reaction. 4.4g of ethylene carbonate, 10.6g of anhydrous methanol and 0.4g of catalyst were added to a double-necked flask. The reaction was stirred in a water bath at 70℃ for 5h. The supernatant was filtered and analyzed for yield by gas chromatography. After the reaction, the catalyst was recovered and activated at high temperature and a cycle experiment was carried out. The results showed that the yield of dimethyl carbonate of sample 3-1 was 42.2%, while the yield of dimethyl carbonate of sample 3-2 was 39.8%, which indicated that the single-atom solid base with nitrogen and sulfur co-coordination had higher catalytic activity. At the same time, after five cycles of use, the yield of sample 3-1 did not show a significant decrease, indicating that the introduction of heteroatom nitrogen and sulfur anchored the calcium atom on the carrier well, giving it good cycle stability.
[0034] Embodiment 4:
[0035] (1) Take 3mmol of pyrrole and 2mmol of 1,3,5-tri-bromomethylbenzene and dissolve them in 120mL of dichloroethane, add 3mmol of ferric chloride, place in a water bath at 80℃ and heat and stir for 36h to obtain a solid precipitate. The sample that is filtered, washed and dried is polymer D, which is carbonized at 500℃ in a nitrogen atmosphere and kept warm for 2h to obtain a nitrogen-doped carbon sample. Weigh 0.7g of thiourea and 0.07g of sodium nitrate in a beaker, add 20mL of ethanol to completely dissolve them, then add 0.2g of nitrogen-doped carbon, stir at room temperature for 12h and evaporate in a water bath, and calcine the obtained sample at 800℃ in an argon atmosphere for 2.5h. After cooling naturally to room temperature, a single atomic sodium solid base catalyst (sample 4-1) is obtained, in which the mass content of nitrogen is 14.8%, the mass content of sulfur is 4.9%, and the mass content of active components is 2.9%. For the convenience of comparison and explanation, comparative samples were prepared by the same preparation method: Sample 4-2 is a single-atom sample coordinated with nitrogen without the addition of thiourea.
[0036] (2) The obtained catalyst was tested for catalytic transesterification reaction. 4.4g of ethylene carbonate, 10.6g of anhydrous methanol and 0.4g of catalyst were added to a double-necked flask. The reaction was stirred for 6h in a water bath at 70℃. The supernatant was filtered and the yield was analyzed by gas chromatography. After the reaction, the catalyst was recovered and activated at high temperature and a cycle experiment was carried out. The results showed that the yield of dimethyl carbonate of sample 4-1 was 47.4%, while the yield of dimethyl carbonate of sample 4-2 was 42.1%, which indicates that the single-atom solid base with nitrogen and sulfur co-coordination has a higher catalytic activity. At the same time, after five cycles of use, the yield of sample 4-1 did not show a significant decrease, indicating that the introduction of heteroatom nitrogen and sulfur anchored the sodium atom on the carrier well, giving it good cycle stability.
Claims
1. A nitrogen-sulfur co-coordinated single-atom solid base catalyst, characterized in that: It is composed of a nitrogen-sulfur co-doped carbon carrier and an active component, wherein the active component is a single alkali metal or alkaline earth metal atom.
2. The single-atom solid base catalyst according to claim 1, characterized in that The mass content of nitrogen in the nitrogen-sulfur co-doped carbon carrier is 5% to 15%, and the mass content of sulfur is 1% to 5%.
3. The single-atom solid base catalyst according to claim 1, characterized in that The active component is calcium, sodium or potassium atom; wherein the mass content of the active component is 0.5% to 3%.
4. A method for preparing the single-atom solid base catalyst as claimed in claim 1, wherein the steps are as follows: (1) taking a certain amount of polymer precursors A and B and dissolving them in an organic solvent, adding ferric chloride catalyst, heating in a water bath and stirring the reaction for a period of time to obtain a solid precipitate, filtering and drying the obtained sample to obtain a polymer; wherein the precursor A is mesitylene or pyrrole; the precursor B is one of methylal, α,α'-dichloro-p-xylene, 1,3,5-tri-bromomethylbenzene or mesitylene alcohol; (2) The polymer is carbonized at high temperature in an inert atmosphere to obtain nitrogen-doped carbon, and then a sulfur source precursor and an active metal precursor are introduced by an impregnation method; the impregnated sample is evaporated in a water bath and then calcined at high temperature in an inert gas to finally form a nitrogen-sulfur co-coordinated single-atom solid base catalyst.
5. The method according to claim 4, characterized in that The organic solvent in step (1) is dichloromethane or tetrahydrofuran; the molar ratio of polymer precursor A to B is 0.6-1.5:1; the molar ratio of catalyst to polymer precursor A is 1-2:1; the reaction temperature is 60-80°C, and the reaction time is 36-90h.
6. The method according to claim 4, characterized in that The temperature of the high-temperature carbonization in step (2) is 450-500°C, and the time of the high-temperature carbonization is 2-2.5 hours; the sulfur source precursor is thiophene or thiourea; the mass ratio of the sulfur source precursor to the nitrogen-doped carbon is 2-3.5:1; the active metal precursor is potassium nitrate, sodium nitrate or calcium nitrate, and the mass ratio of the active metal precursor to the nitrogen-doped carbon is 0.2-0.35:1; the temperature of the high-temperature calcination is 800-900°C, and the time of the high-temperature calcination is 2-2.5 hours.
7. Use of the single-atom solid base catalyst as claimed in claim 1 in producing dimethyl carbonate by ester exchange reaction.
8. The use according to claim 7, wherein the specific reaction steps are as follows: methanol and ethylene carbonate are placed in a double-necked reaction bottle equipped with a condenser, heated in a water bath to a specific temperature, and then a catalyst is added to start the reaction, and the product is obtained after a period of reaction.
9. The use according to claim 8, characterized in that The mass ratio of methanol to ethylene carbonate is 2-2.5:1; the mass ratio of catalyst dosage to ethylene carbonate is 0.04-0.12:1; the reaction temperature is 65-85°C, and the reaction time is 3.5-6.5h.
